Development of Spotify Podcast as an Arabic Listening Media for 11th-Grade Madrasah Aliyah Students - Fairuza Mumtaz; Shofa Musthofa Khalid; Rinaldi Supriadi; Tiara Indah Sari (Mantiqu Tayr: Journal of Arabic Language, 2024)
This research is motivated by the lack of development of innovative learning media for learning Arabic listening at Madrasah Aliyah Al-Inayah Bandung. Additionally, teachers have not fully utilized technology as a learning media. In learning Arabic listening, teachers only use audio players such as MP3 players on cell phones or read the material directly in front of the class. Therefore, this study aims to develop practical and innovative Spotify podcast media for learning Arabic listening in 11th-grade. The type of research used is research and development (R&D) using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects in this study were 27 11th-grade students of Madrasah Aliyah    Al-Inayah Bandung. Data were collected through interviews and questionnaires. The media developed was then validated by experts, with validation results from material experts showing a percentage of 92.7% (very valid), and from media experts 97.7% (very valid). It was also tested on students to assess its feasibility with the results showing a percentage of 88% (very valid). Based on these results, the Spotify podcast media is considered feasible as a learning media for Arabic listening in 11th-grade at Madrasah Aliyah. It is hoped that this will facilitate the learning process, particularly in Arabic listening comprehension, thus creating quality learning experiences. This research is aimed at developing podcast media for Arabic listening skills, and it can serve as a suggestion for future studies to investigate or develop podcasts as a learning media for other Arabic language skills.